THE CHARACTERISTIC OF ERECTILE DYSFUNCTION AMONG TYPE 2 DIABETES MELLITUS MALE IN EASTERN INDONESIA - Zulfiqqar, Andy; Anthonius, Franky Renato; Cyko, Prasetyo Amanda; Nandana, Pandu Ishaq; Yuri, Prahara; Brodjonegoro, Sakti R (Indonesian Journal of Urology, 2021)
Objective: To determine Type-2 diabetic patients and its characteristics to determined risk of Erectile dysfunction (ED) and the role of EHS score as more practical tools to screening ED among T2DM patients. Material & Methods: The cross-sectional observational study was carried out at the Internal medicine Unit of Manambai Abdulkadir and Dompu district Hospital, out of 45 patients were included on this study. The data were collected from June 01 – August 01 2017. A structural questioner was used to collect the data and was analyzed using SPSS 2.0. person analysis correlation and logistic regression were used to find the Odds Ratio (OR). Results: We found that 38 out of 45 (84.4%) patients (mean age 57.2 ± 7.1) have Erectile dysfunction, 26 patients uncontrolled diabetes, 5 (11.1%) treated as CHF, 4 (8.9%) CKD, and 7 (15.6%) neuropathy diabetic. There is high correlation between random glucose level and IIEF-5 score (r=0.5, p=0.01). The overall odd ratio of ED in this studies was 4.3 (95% CI: 0.73 to 25.1) for uncontrolled diabetes, 2.5 (95% CI: 0.1 to 51.1) for Treated CHF, 2 (95% CI: 0.01 to 41.6) for CKD, and it was 1.2 (95% CI: 0.1 to 11.5) for neuropathy diabetics. Conclusion: From this study, we found that most diabetic patients have ED, and there is high correlation between random glucose level and simplified IIEF-5 score, EHS performed similar result on diagnoses ED compared to IIEF-5.